Perceptions and experiences of directly observed treatment in tuberculosis: insights from a mixed-methods cross-sectional study - Diana Amorim; João Pedro Ramos; Pedro Barbosa; Mariana Vieira; Raquel Duarte (Jornal Brasileiro de Pneumologia)
ABSTRACT Objective: The demanding nature and psychosocial burdens of directly observed treatment (DOT) have opened a path to alternative strategies such as video-observed therapy (VOT), which offers comparable treatment outcomes and patient satisfaction while potentially saving time and reducing costs. The objective of this study was to evaluate the perceptions and experiences of patients and health care professionals regarding DOT and other treatment strategies implemented in Portugal. Methods: Patients with a confirmed diagnosis of tuberculosis, treated at the Vila Nova de Gaia Outpatient Tuberculosis Centre in the last two years, were asked to complete a brief questionnaire, as were health care professionals working in the northern region of Portugal. Differences were analysed with chi-square tests, complemented by thematic analysis. Results: A total of 62 individuals completed the questionnaire: 29 health care professionals and 33 patients. There were significant differences between the two groups in their views regarding the impact of DOT on treatment outcomes, with health care professionals perceiving a higher degree of negative effects and patients expressing greater satisfaction. Long travel distances, transportation issues and high costs were some of the challenges mentioned by the patients. Significant differences were also found regarding the role DOT plays in ensuring treatment adherence, with patients emphasising personal responsibility and its importance in preventing loss to follow-up and strengthening relationships with health care professionals. Dose dispensing was favoured for its convenience in specific situations, and VOT was generally preferred to reduce constant travelling. Both parties raised some concerns. Conclusions: Existing discrepancies suggest a misalignment between patient experiences and health care provider perceptions, underscoring the need for enhanced communication and a more nuanced understanding of patient perspectives when designing and implementing different tuberculosis treatment adherence strategies.